Pemanfaatan Spotify sebagai Media Dongeng Digital untuk Meningkatkan Media Pembelajaran Bahasa Indonesia - Putri Saraswati; Didah Nurhamidah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This research discusses the utilization of Spotify in learning as a language teaching medium that opens up new opportunities, especially through fairy tales as a form of oral literature that is rich in cultural values. Fairy tales serve as an effective means to instill moral values, enrich vocabulary, and introduce culture to students. This combination of technology and tradition makes the learning process more interesting and relevant to the times. This study uses a qualitative method with the research subject of 5th semester students of the Indonesian Language and Literature Education Study Program. The results show that the use of Spotify not only introduces cultural wealth, but also instills character values and improves language skills in students.